PENGARUH RATIO PROFITABILITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DALAM JAKARTA ISLAMIC INDEK YANG TERDAFTAR DI BEI PERIODE 2015-2018 - M. Helli; Budi Wahono; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine how the influence of return on equity (ROE), net profit margin (NPM) debt to equity ratio (DER) on stock prices listed in the Jakarta Islamic Index listed on the IDX. This study uses profitability ratios with return on equity (ROE), net profit margin (NPM) variables and uses solvency ratios with debt to equity ratio (DER) variables as variables that show financial performance Based on predetermined sample criteria, the number of samples from companies listed on the Jakarta Islamic index, there are 11 companies that meet the criteria listed on the Indonesia Stock Exchange (IDX). In determining this sample researchers used a purposive sampling method. which is to determine samples with certain criteria. The analysis technique used is descriptive analysis, classic assumption test and Multiple Linear Regression namely with data of research in the form of panel data. The results of this study indicate that partially the Return On Equity (ROE) and Net Profit Margin (NPM) variables have a significant effect on the stock price of company, the Debt to Equity Ratio (DER) variable has no effect on the stock price. And simultaneously all variables have an influence on stock prices. Keywords: Return On Equity (ROE), Net Profit Margin (NPM), Debt To Equity Ratio (DER), and Stock Price